2016
DOI: 10.1038/ncomms13434
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation strengthening of high-temperature superalloys

Abstract: Decades of research has been focused on improving the high-temperature properties of nickel-based superalloys, an essential class of materials used in the hot section of jet turbine engines, allowing increased engine efficiency and reduced CO2 emissions. Here we introduce a new ‘phase-transformation strengthening' mechanism that resists high-temperature creep deformation in nickel-based superalloys, where specific alloying elements inhibit the deleterious deformation mode of nanotwinning at temperatures above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 192 publications
(76 citation statements)
references
References 33 publications
3
72
1
Order By: Relevance
“…The existence of these faults is a consistent proof of the high activity of partial dislocations shearing at these testing conditions (800°C-650 MPa). This high density of faults contrasts with the relatively cleaner microstructures reported by Smith et al [2] presumably explained by the higher level of strain imposed here to the samples studied. The complex dislocation structures extend also to the c-channels where dislocation pile-ups can be observed.…”
Section: Resultscontrasting
confidence: 52%
See 4 more Smart Citations
“…The existence of these faults is a consistent proof of the high activity of partial dislocations shearing at these testing conditions (800°C-650 MPa). This high density of faults contrasts with the relatively cleaner microstructures reported by Smith et al [2] presumably explained by the higher level of strain imposed here to the samples studied. The complex dislocation structures extend also to the c-channels where dislocation pile-ups can be observed.…”
Section: Resultscontrasting
confidence: 52%
“…From these results it arises that shearing by Shockley partial dislocations promotes significantly the plastic flow of the alloy at high temperatures. Therefore, mechanisms that limit the plasticity to just APB shearing are desirable for strengthening the alloy as observed experimentally by Smith et al [2] Additionally, it is noteworthy the higher level of segregation is observed for APB, which may be linked The concentrations at the faults are averaged-integrated assuming the cut-off point to be half of the peak. When several faults of the same type were available (for twins and SESFs), the concentration values are standard-averaged values between the same type of faults.. with the necessity of higher amounts of c-stabilizers in order to lower the energy of the fault.…”
Section: Calculated Velocitiesmentioning
confidence: 99%
See 3 more Smart Citations